Tuesday

March 31, 2015

March 31, 2015

Posted by **lou** on Monday, May 6, 2013 at 9:56pm.

- algebra -
**Reiny**, Monday, May 6, 2013 at 10:24pm(-12a^2b^6)^3 / (9a^3b^9)^3

= ( (-12a^2b^6)/(9a^3b^9) )^3

= ( (-4/3)(1/a)(1/b^3) )^3

= (-64/27)(1/a^3)(1/b^9)

= -64/( 27a^3b^9 )

**Answer this Question**

**Related Questions**

algebra - simplify -2a^+6ab^-12a^b/-24ab the b -12a^b the b is to the third ...

algebra - simplify 2a^2 + 6ab^2-12a^2b^3 divided by 24ab -2a^2/-24ab + 6ab^2/...

mathematics - 12a^2b over 4 times 4a+8b over 20a^2b^3

algebra - -12a+3(2a+1)=-6a

algebra 2 - If f(3a-1) = 12a-7, what is f(x)?

Algebra 1 (Reiny) - 12a - 11 = 9a - 1?

Algebra - (9a^3b^4-12a^2b^5+6ab^7)/(6a^2b^3)

Algebra II - Factor: 12a^2-17a-5

algebra - 12a-18b/-6 simplify

algebra 1 help - 6(-3-2)^2 over -3^2-2(-3)(2)+2^2 6(-3-2)^2 over -3^2-2(-3)(2)+2...